Одно письмо П. А. Вяземского [One Letter by Pyotr Vyazemsky] - Sobolev, Lev (Slavica Revalensia, 2019)
This is a prefaced and annotated preprint of a much larger corpus of Prince Pyotr Vyazemsky’s letters to the editor of the journal “Russkii arkhiv” (“Russian Archive”) Pyotr Bartenev. In this particular letter of the 6th (18th) of February, 1877, Pyotr Vyazemsky discusses some editorial matters, and reveals his caution towards his correspondent’s sentiment triggered by the Serbo-Turkish war: “Kruppovskie pushki i molitva ne ladiat mezhdu soboi” (“Krupp guns and prayers do not get along with each other”).